4. Kazeem Olojo: A Professional Painter and an Art Instructor Universal Studios of Art, Lagos, Nigeria - Bardi Augustine Okola (Sciendo, 2017)
The works of art are priceless going by the quality of works exhibited by an artist. The artist tends to describe a particular scene near to the natural object in question. In the 15th and 16th centuries , France relayed on the impressionists who graduated from workshops and schools of apprentice in the likes of Gauguin, Monet, Manet, Degas, Renoir Cezanne, Delacroix and others to capture scenes of the Parisian country side that existed long age. The artist and his works remain indispensible to the existing societies. This form of art venture is not new to Nigeria where schools and workshops of apprenticeship exist. In Nigeria, the existing heritage and traditions if not for the artists will not be translated into art by the artists particularly painters like Dale, Oshinowo, Oguntokun, Emokpae, El-Dragg and others. The existence of workshops and schools of learning art have trained more artists to keep the aesthetical values of art. The society would be no doubt an unpleasant community without a touch of the arts. The artists who on daily bases create by painting, sculpting to make the environment a pleasurable place remain an important factor in the society.